Developing Mobile-Assisted Language Learning (MALL) Materials for ESL Learners - Sanjaya, Eko (Proceedings International Conference on Teaching and Education (ICoTE), 2024)
The development of technology has brought significant impacts on education. This creates much potential for the teaching and learning of English as a second language. With the great capability of the internet, educators can design powerful materials for efficient and effective learning. Mobile-assisted Language Learning (MALL) has become one of the popular research areas on technology in education in recent years for its advantages of flexibility of time and place. However, much only focus on a single application or platform implementation for the learning. This proposed study intends to integrate multiple internet-based platforms to support ESL learning. It aims to develop attractive and interactive learning materials that utilize Mobile-assisted Language Learning. This research uses the ADDIE method in developing the materials. To evaluate the materials, Technology Acceptance Model (TAM) will be adopted to investigate the participants"™ perceptions of their experience of using the MALL materials. The participants of the study will be 7th-grade students of SMPN 4 Satap Sejangkung. These materials are planned to be a product that can make use of the advantages of mobile devices, in this case, flexibility and usability.